PERBANDINGAN ANALISA DEBIT BANJIR PADA SUNGAI MENCONGAH KABUPATEN LOMBOK BARAT: Comparison Of Flood Discharge Analysis In The Mengagah River Kabupaten Lombok Barat - Suta, I Gede Junianta; Yamin, Muhamad; Seventilova, I G N Octava; Aminullah, Aminullah (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2024)
Many unit hydrograph concepts are used to carry out the transformation from rainfall to flow discharge. The data needed to derive a measured unit hydrograph in the watershed under consideration is automatic rainfall data and discharge recording at certain observation points. A hydrograph can be described as a graphic presentation of one of the elements of flow and time. The purpose of the design flood discharge analysis is to evaluate the magnitude of the design flood discharge at various return periods of  2, 5, 10, 20, 25, 50, 100 years. This research is a case study using rainfall data for 10 years, namely 2014-2023. Next, an analysis of the maximum daily rainfall in the Mencongah watershed (watershed) was carried out, climatological data obtained from the relevant agencies. After analyzing the rainfall data obtained in the field, the maximum annual rainfall in the Mencongah watershed was obtained based on the results of data analysis from the Mencongah station, which was 229 mm, while the average rainfall was 167.9 mm, a large value.PMP (Probable Maximum Precipitation) on the Mencongah river is 85.37 mm, the design flood discharge with return periods of 2, 5, 10, 20, 25, 50 and 100 years using the Hapers method is obtained respectively: 72.21 m³; 180.525 m³, 361.05 mm, 722.101 m³, 902.626 m³, 1805.252 m³, 3610.504 m³,while the Melchior method discharge is 191,517 m³; 478,793 m³; 957,586 m³; 1915.171 m³; 2393,964 m³; 4787 m³; and 9575.855 m³